Precision measurement of the $B^{0}_{s}$-$\bar{B}^{0}_{s}$ oscillation frequency with the decay $B^{0}_{s}\rightarrowD^{-}_{s}π^{+}$ - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
A key ingredient to searches for physics beyond the Standard Model in $B^{0}_{s}$ mixing phenomena is the measurement of the $B^{0}_{s}$-$\bar{B}^{0}_{s}$ oscillation frequency, which is equivalent to the mass difference $Δ m_{s}$ of the $B^{0}_{s}$ mass eigenstates. Using the world's largest $B^{0}_{s}$ meson sample accumulated in a dataset, corresponding to an integrated luminosity of 1.0 fb$^{-1}$, collected by the LHCb experiment at the CERN LHC in 2011, a measurement of $Δ m_{s}$ is presented. A total of about 34,000 $B^{0}_{s}\rightarrowD^{-}_{s}π^{+}$ signal decays are reconstructed, with an average decay time resolution of 44 fs. The oscillation frequency is measured to be \mbox{$Δ m_{s}$ = 17.768 $±$ 0.023 (stat) $±$ 0.006 (syst) ps$^{-1}$}, which is the most precise measurement to date.